Evaluation of serum lipid, lipoprotein, and apolipoprotein levels in psoriatic patients: a systematic review and meta-analysis of case-control studies - Ramezani, Mazaher (Postepy Dermatol Alergol, 2019)
INTRODUCTION: Psoriasis is a T cell-mediated inflammatory skin disease in which fatty acids may be a link between psoriasis and its comorbidity. AIM: The present meta-analysis aimed to evaluate lipid, lipoprotein, and apolipoprotein levels in the psoriatic patients compared with the control subjects. MATERIAL AND METHODS: Four databases, including Web of Science, Scopus, PubMed, and Cochrane Library were searched until July 2017. All records analysed were case-control studies. The quality of the questionnaires was evaluated using the Newcastle-Ottawa Scale (NOS). A random-effects meta-analysis was done by Rev Man 5.3 using mean difference (MD) and 95% confidence intervals (CIs). RESULTS: Out of 580 studies identified in four databases, 49 studies were included and analysed in this meta-analysis. The results showed that MD of total cholesterol, triglyceride, LDL, VLDL, HDL, Lp(a), Apo A1, and Apo B levels in the patients compared with the controls were (MD = 13.74 mg/dl; 95% CI: 7.72–19.75; p< 0.00001), (MD = 26.04 mg/dl; 95% CI: 20.77–31.31; p< 0.00001), (MD = 11.41 mg/dl; 95% CI: 6.26–16.57; p< 0.0001), (MD = 4.82 mg/dl; 95% CI: 3.63–6.00; p< 0.00001), (MD = –2.78 mg/dl; 95% CI: –4.53 – –1.03; p< 0.002), (MD = 8.51 mg/dl; 95% CI: 4.86–12.17; p< 0.0001), (MD = –6.60 mg/dl; 95% CI: –13.96 – 0.75; p< 0.08), and (MD = 9.70 mg/dl; 95% CI: 3.02–16.39; p< 0.004), respectively. CONCLUSIONS: This meta-analysis identified abnormality of serum lipid, lipoprotein, and apolipoproteinprofiles in psoriatic patients compared with the controls as well as possibly a greater risk of atherosclerosis and cardiovascular (CV) accidents in the patients.